Bridging the Gap: EFL Lecturers’ Familiarity and Knowledge of Technology in Language Teachings - Rahmat, Subhan; Noni, Nurdin; Sunra, La; Halim, Abd. (Journal of English Language Teaching, Literature and Culture, 2025)
The rapid growth of digital technology has significantly influenced the landscape of higher education, including English as a Foreign Language (EFL) instruction. However, many lecturers still struggle to integrate technology effectively into their pedagogy. This study investigates EFL lecturers’ technological familiarity and knowledge in a maritime higher education context, aiming to identify their level of technological competence and the underlying factors influencing technology use in teaching. Employing a quantitative research design, data were collected through a questionnaire administered to 15 lecturers from a maritime higher education institution in Indonesia. The findings revealed that lecturers possess moderate familiarity with digital tools such as learning management systems and video conferencing platforms. However, their pedagogical integration of technology remains limited, with most using it mainly for material delivery rather than interactive or student-centered learning. The analysis indicates that the lecturers’ technological knowledge (TK) has not yet been sufficiently linked with pedagogical (PK) and content knowledge (CK), as conceptualized in the Technological Pedagogical and Content Knowledge (TPACK) framework. Barriers such as insufficient infrastructure, lack of institutional support, and limited digital pedagogical understanding were found to hinder optimal technology integration. The study suggests that sustainable professional development programs focusing on digital pedagogy and contextualized training are essential to enhance lecturers’ competence in integrating technology for effective EFL instruction in maritime education.